Rehabilitation of Diffuse Axonal Injury Deficit Caused by Traumatic Brain Injury Through Ayurvedic Treatment Protocol- A Case Study. - Mahajan, Deepak (European Journal of Applied Sciences, 2022)
One of the most important types of brain damage that can occur as a result of non-missile head injury is diffuse axonal injury. Though DAI is a histological diagnosis, clinically it may be defines as a state of unconsciousness lasting for minimum 6 hours or more after traumatic brain injury except cases of swelling or ischemic brain lesions. DAI is the considered the most important factor in determining the morbidity and mortality in the traumatic brain injury. DIA causes behavioral, physical, and cognitive changes that effect on social and personal life of a patient also quality of life of patients and their families is affected. Ayurveda describes Head as a marma point. Head injury is termed as Shiromarma abhigata in Ayurveda classical books. Ayurveda treats this with the help of some herbal remedies and Panchakarma like Snehan, Pinda sweda, Nasya, Basti and Marma therapy